ChemInform Abstract: Organic Azides: "Energetic Reagents" for the Intermolecular Amination of C—H Bonds. Issue 45 (23rd October 2014) - Intrieri, Daniela; Zardi, Paolo; Caselli, Alessandro; Gallo, Emma
Abstract Review: 71 refs.